MOFs derived hard carbon material, preparation method thereof and application of MOFs derived hard carbon material in sodium ion battery

The Zn-MOF precursor was prepared by microwave heating and calcined at high temperature, which solved the problem of long and high cost of preparation of hard carbon materials. The hard carbon material with a porous structure was obtained, and used in sodium ion batteries were used, which significantly improved the electrochemical performance of the battery. and cycle life.

CN119153688APending Publication Date: 2024-12-17HEFEI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411072966.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing hard carbon material preparation methods are time-consuming, costly and low yields, making it difficult to meet the needs of sodium ion battery negative electrode materials, especially in improving energy density and cycle life.

Method used

The Zn-MOF precursor is prepared by microwave heating reaction, and then calcined at high temperature under the protection of inert gas to obtain MOFs-derived hard carbon materials with porous structures, simplifying the process flow and reducing production costs.

Benefits of technology

It has achieved rapid and low-cost preparation of hard carbon materials with large specific surface area and excellent electrochemical performance. It is suitable for sodium ion batteries, improving the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153688A_ABST
    Figure CN119153688A_ABST
Patent Text Reader

Abstract

The invention discloses an MOFs derived hard carbon material and a preparation method and application thereof, and relates to the technical field of new energy materials, and the preparation method comprises the following steps: (1) preparing a Zn-MOF precursor from a zinc salt and an organic ligand through a microwave heating reaction; and (2) carrying out high-temperature calcination on the Zn-MOF precursor under the protection of inert gas to prepare the hard carbon material. The preparation method of the hard carbon material provided by the invention has the characteristics of simplicity and convenience in operation, low cost, short production period and the like, and industrial production is convenient to realize; and the prepared hard carbon material has good electrochemical performance and can be directly applied to the fields of energy storage and catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a MOFs-derived hard carbon material, a preparation method thereof, and an application thereof in a sodium ion battery. Background Art

[0002] As the world's reliance on renewable energy increases, energy storage technology becomes critical. Sodium-ion batteries are seen as an important complement to lithium-ion batteries due to their cost-effectiveness and the wide distribution of sodium resources, especially in large-scale energy storage systems. Sodium-ion battery technology has made significant progress in the past few years, but its energy density and cycle life still need to be further improved to meet market demand.

[0003] As a key factor affecting battery performance, negative electrode materials have always been a hot topic of research. Traditional graphite materials perform poorly in sodium-ion batteries because sodium ions have a large ionic radius and are difficult to embed into the graphite structure. Although alloy negative electrode materials have high theoretical capacity, they have problems with volume expansion and poor cycle stability during charging and discharging. Hard carbon is considered to be a promising negative electrode material for sodium-ion batteries due to its structural diversity and excellent cycle stability. Hard carbon materials have a high specific surface area and porosity, which facilitates the rapid diffusion and storage of sodium ions.

[0004] In order to realize the commercial application of hard carbon materials, it is necessary to develop fast and cost-effective synthesis methods. This will not only speed up the transition from laboratory to industrial production, but also reduce production costs and improve the market competitiveness of materials. At present, researchers have developed a variety of methods for synthesizing hard carbon materials, including template method, chemical vapor deposition method and direct pyrolysis. However, these methods often have the problems of long time, high cost and low yield. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a MOFs-derived hard carbon material. The preparation method has the characteristics of simple operation and short reaction time, and the prepared hard carbon material has a porous structure and a large specific surface area. It can be used as a negative electrode material in sodium ion batteries and exhibits excellent electrochemical properties.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a MOFs-derived hard carbon material, comprising the following steps:

[0008] (1) preparing a Zn-MOF precursor by reacting a zinc salt with an organic ligand through microwave heating;

[0009] (2) The Zn-MOF precursor is prepared by high-temperature calcination under inert gas protection.

[0010] The second object of the present invention is to provide a MOFs-derived hard carbon material prepared by the aforementioned preparation method.

[0011] The third object of the present invention is to provide application of the MOFs-derived hard carbon material in sodium ion batteries.

[0012] The beneficial effects of the present invention are:

[0013] (1) The present invention can prepare a two-dimensional sheet-like Zn-MOF precursor in a short time through microwave-assisted reaction, and then the precursor Zn-MOF is calcined at high temperature to obtain a porous two-dimensional sheet-like hard carbon material with a large specific surface area.

[0014] (2) The hard carbon material preparation method provided by the present invention has the characteristics of simple operation, low cost, short production cycle, etc., which is convenient for industrial production.

[0015] (3) The hard carbon material prepared by the present invention has good electrochemical properties and can be directly applied in the fields of energy storage and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the Zn-MOF precursor prepared in Example 1;

[0017] Figure 2 This is the X-ray diffraction pattern of the hard carbon material prepared in Example 1;

[0018] Figure 3 This is the Raman spectrum of the hard carbon material prepared in Example 1;

[0019] Figure 4 This is a scanning electron microscope image of the hard carbon material prepared in Example 1;

[0020] Figure 5 The adsorption-desorption isotherm and pore size distribution diagram of the hard carbon material prepared in Example 1;

[0021] Figure 6 This is a cycle performance diagram of a sodium ion battery assembled using the hard carbon material prepared in Example 1 as the negative electrode material at a current density of 0.5C;

[0022] Figure 7 The figure shows the charge and discharge curves of a sodium ion battery assembled with the hard carbon material prepared in Example 1 as the negative electrode material after different cycle times at a current density of 0.5C. DETAILED DESCRIPTION

[0023] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0024] The present invention provides a method for preparing a MOFs-derived hard carbon material, comprising the following steps:

[0025] (1) preparing a Zn-MOF precursor by reacting a zinc salt with an organic ligand through microwave heating;

[0026] (2) The Zn-MOF precursor is prepared by high-temperature calcination under inert gas protection.

[0027] Furthermore, the zinc salt is selected from at least one of zinc nitrate hexahydrate, zinc chloride hexahydrate, zinc acetate and zinc sulfate.

[0028] Furthermore, the organic ligand is selected from at least one of aromatic dianhydride and phthalocyanine derivatives.

[0029] Preferably, the aromatic dianhydride is selected from at least one of 1,4,5,8-naphthalenetetracarboxylic anhydride, phthalic anhydride, pyromellitic anhydride, terephthalic anhydride, tetrafluorophthalic anhydride, 2,3,6,7-tetrafluorophthalic anhydride and 2,3-dichlorophthalic anhydride.

[0030] Preferably, the phthalocyanine derivative is at least one selected from α-tetranitrophthalocyanine, α-tetraaminophthalocyanine, β-tetraaminophthalocyanine, β-tetraisocyanatephthalocyanine, and α-tetrahydroxyphthalocyanine.

[0031] Furthermore, the power of the microwave heating reaction is 800-1000W, the temperature is 40-70°C, the heating rate is 5-30°C / min, and the time is 10-30min.

[0032] After the microwave heating reaction in step (3) is completed, the reaction solution is allowed to stand, the precipitate is centrifuged, washed, and dried to obtain a Zn-MOF precursor. The washing step is washing with deionized water and ethanol in sequence, and the drying step is vacuum drying at a drying temperature of 60 to 100° C. and a drying time of 8 to 16 hours.

[0033] Furthermore, the inert gas is an inert gas commonly used in the art, such as argon and helium, and argon is preferred because it is relatively cheap.

[0034] Furthermore, the high temperature calcination temperature is 700-900°C, the time is 1-3h, and the heating rate is 3-10°C / min.

[0035] The material of the reaction vessel involved in the preparation method of the MOFs-derived hard carbon material of the present invention is a material that does not react with zinc salts, organic ligands, solvents and carbon, and specifically polytetrafluoroethylene commonly used in the art can be selected.

[0036] The present invention provides a MOFs-derived hard carbon material prepared by the aforementioned preparation method.

[0037] Furthermore, the specific surface area of ​​the MOFs-derived hard carbon material is greater than 500 m 2 / g, pore size is 1.0~2.0nm.

[0038] The present invention also provides the use of the MOFs-derived hard carbon material in a sodium ion battery. The MOFs-derived hard carbon material of the present invention can not only be directly used as a negative electrode material of a sodium ion battery, but also can be used as a coating material for a positive electrode of a sodium ion battery.

[0039] Example 1

[0040] (1) Disperse and dissolve 300 mg of zinc nitrate hexahydrate in 10 mL of deionized water to obtain solution A.

[0041] (2) Add 120 mg of 1,4,5,8-naphthalenetetracarboxylic anhydride to 50 mL of a 0.03 mol / L sodium hydroxide solution and disperse by ultrasonic for 10 min to obtain solution B.

[0042] (3) Solution A was added dropwise to solution B at a speed of 600 r / min and a temperature of 60°C to obtain solution C.

[0043] (4) Pour solution C into a microwave reactor, and then place the microwave reactor in a multifunctional microwave hydrothermal parallel synthesizer. Perform microwave reaction for 30 min at a power of 1000 W, a heating rate of 10 °C / min, and a temperature of 60 °C. After the reaction is completed, the reaction solution is naturally cooled to room temperature and the precipitate is collected.

[0044] (5) The precipitate was centrifuged at 12000 rpm for 2 min to separate the mother liquor. The obtained product was washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a Zn-MOF precursor.

[0045] (6) The Zn-MOF precursor was loaded into a porcelain boat, and the porcelain boat was placed in a tubular furnace. Under argon protection, the temperature was increased to 900°C at a heating rate of 3°C / min and kept at this temperature for 3 h. After the tubular furnace was cooled to room temperature, a black product was obtained.

[0046] from Figure 1 It can be seen that the microstructure of the Zn-MOF precursor prepared in Example 1 is in the form of multiple clustered flowers, and the clustered flowers are assembled from multiple nanosheets.

[0047] from Figure 2It can be seen that the two diffraction peaks of the product prepared in Example 1 at 23-26° and 43-44° are consistent with the diffraction peaks corresponding to carbon, indicating that the product is hard carbon.

[0048] from Figure 3 It can be seen that the Raman test results of the product prepared in Example 1 are d / I g The ratio is 2.15, indicating that the product is hard carbon with a high degree of defects.

[0049] from Figure 4 It can be seen that the morphology of the Zn-MOF precursor prepared in Example 1 did not change after carbonization and still maintained a flower shape.

[0050] from Figure 5 It can be seen that the specific surface area of ​​the hard carbon material prepared in Example 1 is 536.2 m 2 / g, and has micropores with a pore size of 1.0 to 2.0 nm.

[0051] The hard carbon material prepared in Example 1 was ground and mixed with carbon black Super P and carboxymethyl cellulose in a mass ratio of 8:1:1, and then prepared into a slurry with deionized water and evenly coated on the copper current collector, dried in a vacuum drying oven at 80°C for 12 hours, rolled (pressure of 15t), and cut into circular pole pieces with a diameter of 1.2cm using a Kejing slicer. The pole piece was brought into the glove box for battery assembly. The glove box needed to be kept in a complete vacuum state during the entire assembly process. The electrolyte was sodium hexafluorophosphate with a concentration of 1moL / L, the electrolyte was diethylene glycol dimethyl ether, the metal sodium sheet was used as the counter electrode, the diaphragm was glass fiber (Whatman GF / D), and the button battery shell used CR2016. The electrochemical performance test was carried out on the LAND system, and the battery charge and discharge voltage range was 0.01~2V.

[0052] from Figure 6 It can be seen that at a current density of 0.5C, the first-cycle reversible specific capacity of the sodium ion battery assembled with the hard carbon material prepared in Example 1 as the negative electrode material is 474.1 mAh / g, and the first coulombic efficiency is 72.8%; the reversible specific capacity after 100 cycles is 282.9 mAh / g, and the coulombic efficiency is close to 100%.

[0053] from Figure 7 It can be seen that at a current density of 0.5C, the voltage platform of the sodium ion battery assembled using the hard carbon material prepared in Example 1 as the negative electrode material does not change substantially after 100 cycles.

[0054] Example 2

[0055] (1) Disperse and dissolve 300 mg of zinc nitrate hexahydrate in 5 mL of deionized water to obtain solution A.

[0056] (2) Add 150 mg of 1,4,5,8-naphthalenetetracarboxylic anhydride to 50 mL of a 0.025 mol / L sodium hydroxide solution and disperse by ultrasonic for 10 min to obtain solution B.

[0057] (3) Solution A was added dropwise to solution B at a rotation speed of 600 r / min and a temperature of 50° C. to obtain solution C.

[0058] (4) Pour solution C into a microwave reactor, and then place the microwave reactor in a multifunctional microwave hydrothermal parallel synthesizer. Perform microwave reaction for 20 min at a power of 900 W, a heating rate of 20 °C / min, and a temperature of 50 °C. After the reaction is completed, the reaction solution is naturally cooled to room temperature and the precipitate is collected.

[0059] (5) The precipitate was centrifuged at 12000 rpm for 2 min to separate the mother liquor. The obtained product was washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a Zn-MOF precursor.

[0060] (6) The Zn-MOF precursor was loaded into a porcelain boat, and then the porcelain boat was placed in a tubular furnace. Under argon protection, the temperature was increased to 850°C at a heating rate of 5°C / min and kept at that temperature for 2 h. After the tubular furnace was cooled to room temperature, a hard carbon material was obtained.

[0061] Example 3

[0062] (1) Disperse and dissolve 300 mg of zinc nitrate hexahydrate in 5 mL of deionized water to obtain solution A.

[0063] (2) Add 200 mg of 1,4,5,8-naphthalenetetracarboxylic anhydride to 50 mL of a 0.03 mol / L sodium hydroxide solution and disperse by ultrasonic for 10 min to obtain solution B.

[0064] (3) Solution A was added dropwise to solution B at a speed of 600 r / min and a temperature of 50°C to obtain solution C.

[0065] (4) Pour solution C into a microwave reactor, and then place the microwave reactor in a multifunctional microwave hydrothermal parallel synthesizer. Perform microwave reaction for 10 min at a power of 800 W, a heating rate of 30 °C / min, and a temperature of 70 °C. After the reaction is completed, the reaction solution is naturally cooled to room temperature and the precipitate is collected.

[0066] (5) The precipitate was centrifuged at 12000 rpm for 2 min to separate the mother liquor. The obtained product was washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a Zn-MOF precursor.

[0067] (6) The Zn-MOF precursor was loaded into a porcelain boat, and then the porcelain boat was placed in a tubular furnace. Under argon protection, the temperature was increased to 800°C at a heating rate of 10°C / min and kept at that temperature for 2 h. After the tubular furnace was cooled to room temperature, a hard carbon material was obtained.

[0068] Comparative Example 1

[0069] Patent CN 202210587511.2 "A MOF-derived two-dimensional microporous carbon nanosheet material and its preparation method" uses 1,4,5,8-naphthalenetetracarboxylic anhydride and zinc nitrate hexahydrate as raw materials, and heats to 30-80°C to react and prepare a Zn-MOF precursor. The Zn-MOF precursor is calcined at high temperature to obtain a two-dimensional microporous carbon nanosheet material. In this patent, carbon nanosheets are used as carriers and composited with nano-selenium to obtain a two-dimensional C / Se composite material as a positive electrode material for potassium ion batteries. Compared with this patent, the present invention uses a microwave method to react the raw materials to generate a precursor within 10 minutes, greatly shortening the preparation time; on the other hand, the prepared hard carbon material is used as a negative electrode material for sodium ion batteries, so that the sodium ion battery has good electrochemical properties.

[0070] Comparative Example 2

[0071] Patent CN 202311434703.0 "Preparation method of asphalt-based hard carbon material and its application in the negative electrode of sodium ion battery" mixes asphalt and conductive carbon evenly to obtain a mixture, and carbonizes the mixture to obtain asphalt-based hard carbon. Although the asphalt-based hard carbon material prepared by this patent can be used as the negative electrode material of sodium ion battery, the attached Figure 4 It can be seen that the electrochemical performance of its sodium ion battery is far lower than that of Example 1.

[0072] Comparative Example 3

[0073] Patent No. CN201711308255.4 "Hard carbon prepared from biomass waste bagasse and its preparation method and application", takes dried bagasse and performs ball milling to obtain bagasse powder; the bagasse powder is carbonized to obtain hard carbon material. Although the hard carbon material prepared by this patent can be used as a negative electrode material for sodium ion batteries, the attached Figure 3 It can be seen that the electrochemical performance of its sodium ion battery is far lower than that of Example 1.

[0074] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a MOFs-derived hard carbon material, characterized in that: The following steps are involved: (1) preparing a Zn-MOF precursor by reacting a zinc salt with an organic ligand through microwave heating; (2) The Zn-MOF precursor is prepared by high-temperature calcination under inert gas protection.

2. The preparation method according to claim 1, characterized in that: The zinc salt is at least one of zinc nitrate hexahydrate, zinc chloride hexahydrate, zinc acetate and zinc sulfate.

3. The preparation method according to claim 1, characterized in that: The organic ligand is at least one of aromatic dianhydride and phthalocyanine derivative.

4. The preparation method according to claim 3, characterized in that: The aromatic dianhydride is at least one of 1,4,5,8-naphthalenetetracarboxylic anhydride, phthalic anhydride, pyromellitic anhydride, terephthalic anhydride, tetrafluorophthalic anhydride, 2,3,6,7-tetrafluorophthalic anhydride and 2,3-dichlorophthalic anhydride.

5. The preparation method according to claim 3, characterized in that: The phthalocyanine derivative is at least one of α-tetranitrophthalocyanine, α-tetraaminophthalocyanine, β-tetraaminophthalocyanine, β-tetraisocyanatephthalocyanine and α-tetrahydroxyphthalocyanine.

6. The preparation method according to claim 1, characterized in that: The microwave heating reaction has a power of 800-1000W, a temperature of 40-70°C, a heating rate of 5-30°C / min, and a time of 10-30min.

7. The preparation method according to claim 1, characterized in that: The high temperature calcination temperature is 700-900° C., the time is 1-3 hours, and the heating rate is 3-10° C. / min.

8. A MOFs-derived hard carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. The MOFs-derived hard carbon material according to claim 8, characterized in that: The specific surface area of ​​the MOFs-derived hard carbon material is greater than 500 m 2 / g, pore size is 1.0~2.0nm.

10. Use of the MOFs-derived hard carbon material according to claim 8 or 9 in sodium ion batteries.